Article Review: Testing for Detection of Low Pig DNA (Porcine) in Cosmetic Products and Health Supplements - Syafitri, Raden Indah Puspita; Karimah, Naqiyyah Fil Ayatil; Mita, Soraya Ratnawulan (Indonesian Journal of Pharmaceutics, 2023)
The increase in the Muslim population in the world has made the halal product industry grow rapidly. Currently, halal food has the largest proportion in the global market for halal products, followed by cosmetic and pharmaceutical products as the main sector. In the raw materials used for capsule shells and the manufacture of cosmetics, many ingredients come from non-halal sources, for example gelatin, fatty acids, glycerin, and collagen that come from pigs. However, the presence of pork ingredients in medicines, health supplements and cosmetics is prohibited in certain religions such as Islam, therefore the detection of lard in cosmetic products and other pharmaceutical products plays an important role for the benefit of Muslim consumers. Many methods have been developed to detect pork content in highly processed products, one of which is the DNA-based method. This literature review was created based on the aforementioned reason to explain DNA isolation methods and detection that can be used for pig DNA analysis. A literature search was carried out through online databases and 14 research journals were found that met the inclusion criteria. From the research data, it is proven that DNA-based methods such as Polymerase Chain Reaction and its modifications can detect the presence of porcine DNA in products such as cosmetics and food supplements. The selection of DNA detection and isolation methods is based on the type of sample being tested.